Urinary stone ablation with a thulium fibre laser: a rate-of-completion evaluation - I. A. Arbuzov; V. S. Chernega (Вестник урологии, 2023)
Introduction. The main disadvantage of using the rate of ablation of urinary stones as a parameter of thulium lithotripsy is the dependence of this parameter on the energy and frequency of laser pulses. Therefore, the results of measurements of this parameter by researchers differ significantly, since they were carried out at different values of the energy and pulse frequency, as well as at different values of the radiographic density of stones.Objective. To develop a universal indicator to assess the specific value of reducing the mass of urinary stones when performing laser lithotripsy.Materials & methods. We have analyzed scientific publications in domestic and foreign specialized publications (2005 to 2023) related to the measurement of urinary stone ablation rate during thulium laser lithotripsy. We used physical methods of estimation of specific values when we developed a universal indicator of specific value of stone mass reduction.Results. Having processed the data, we obtained the average value of the specific indicator of urinary stone mass reduction per unit of pulse energy during thulium lithotripsy in the ‘dusting mode’, equal to 0.059 ± 0.003 mg/J. The article provides a formula for calculating the "pure" time of lithotripsy, as well as examples of calculating the specific indicator of the stone mass reduction and the time of lithotripsy.Conclusion. This value can be used both to evaluate the efficiency of thulium laser lithotripsy and to predict the time of lithotripsy.